A comparative study of the university curriculum for the Department of Art Education between Iraq and Saudi Arabia (Journal of the College of Basic Education, 2022)
In this study, the curriculum of the Department of Art Education in Iraq and Saudi Arabia was compared in terms of the four elements of the curriculum (goals, content, teaching methods, and evaluation methods).This study aims to:1. Identifying the reality of education in the Department of Art Education in the Republic of Iraq and the Kingdom of Saudi Arabia.2. A review of the methodologies of the Department of Art Education in the Republic of Iraq and the Department of Art Education in the Kingdom of Saudi Arabia.3. Make a comparison between the curricula of the Department of Art Education in the Republic of Iraq and the same department in the Kingdom of Saudi Arabia, and indicate the similarities and differences between the two curricula.4. Reaching recommendations for the development of the Iraqi curriculum.